1997
DOI: 10.1523/jneurosci.17-06-01940.1997
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Membrane Potential Changes Induced by Glucose Deprivation in Striatal Spiny Neurons and in Large Aspiny Interneurons

Abstract: We have studied the electrophysiological effects of glucose deprivation on morphologically identified striatal neurons recorded from a corticostriatal slice preparation. The large majority of the recorded cells were spiny neurons and responded to aglycemia with a slow membrane depolarization coupled with a reduction of the input resistance. In voltage-clamp experiments aglycemia caused an inward current. This current was associated with a conductance increase and reversed at Ϫ40 mV. The aglycemia-induced membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 53 publications
8
57
2
Order By: Relevance
“…Prolonged aglycemia (15-30 min) depolarizes spiny neurons while it hyperpolarizes large aspiny interneurons; both of these membrane potential changes are mediated by postsynaptic mechanisms. Interestingly, adenosine A1 receptor antagonists reduced the aglycemia-induced presynaptic inhibitory effect (present study), but they did not antagonize the postsynaptic changes observed in these two striatal subpopulations during glucose deprivation (Calabresi et al, 1997b). Accordingly, it has been reported that A1 receptor antagonism can delay the hypoxiainduced depression of synaptically evoked excitatory potentials in hippocampal slices (Fowler, 1989;Katchman and Hershkowitz, 1993;Khazipov et al, 1995).…”
Section: Comparison With Other Studiescontrasting
confidence: 60%
See 1 more Smart Citation
“…Prolonged aglycemia (15-30 min) depolarizes spiny neurons while it hyperpolarizes large aspiny interneurons; both of these membrane potential changes are mediated by postsynaptic mechanisms. Interestingly, adenosine A1 receptor antagonists reduced the aglycemia-induced presynaptic inhibitory effect (present study), but they did not antagonize the postsynaptic changes observed in these two striatal subpopulations during glucose deprivation (Calabresi et al, 1997b). Accordingly, it has been reported that A1 receptor antagonism can delay the hypoxiainduced depression of synaptically evoked excitatory potentials in hippocampal slices (Fowler, 1989;Katchman and Hershkowitz, 1993;Khazipov et al, 1995).…”
Section: Comparison With Other Studiescontrasting
confidence: 60%
“…Longer periods of aglycemia (15-30 min) were required to induce postsynaptic changes. We recently have characterized these postsynaptic changes in two neuronal striatal subtypes (Calabresi et al, 1997b). Prolonged aglycemia (15-30 min) depolarizes spiny neurons while it hyperpolarizes large aspiny interneurons; both of these membrane potential changes are mediated by postsynaptic mechanisms.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Diabetes 56:2893-2900, 2007 T he counterregulatory response to hypoglycemia is essential for life and particularly important for insulin-treated diabetic subjects; however, the underlying mechanisms remain largely unknown (1)(2)(3). The existence of low glucose-sensitive neurons in ventromedial and lateral hypothalamus (glucose-inhibited neurons) (3)(4)(5), as well as in other brain areas (6), is well documented; nevertheless, there is also considerable evidence suggesting that peripheral glucose control is necessary for the proper adaptation to hypoglycemia. Besides ␣-cells of the pancreas, systemic low-glucose receptors have been proposed to exist at the portal vein (7) and in the carotid body (CB) (8 -11).…”
Section: Research Design/methods and Results-removalmentioning
confidence: 99%
“…Tandem pore K ϩ channels have, however, been suggested to mediate inhibition of orexin neurons by glucose (5). Depolarization of striatal spiny neurons with glucose deprivation has been attrib- uted to either inactivation of the Na ϩ /K ϩ pump or to potentiation of a nonselective cationic conductance (6,20). It is therefore possible that the Na ϩ -permeable channels generating the receptor potential in CB cells also participate in the depolarization of low glucose-sensitive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Certain brain areas and also specific neuronal subtypes differ significantly in their susceptibility to injury in the course of acute and chronic disorders, suggesting that specific protective factors are expressed differently among neurons or even among different cell types in the same tissue. This can be clearly seen in the striatum, where GABAergic projection cells (12,(14)(15)(16), but not cholinergic interneurons, are precociously damaged in the course of HD (12,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 98%